The Social-Psychological Implications of a Coaching Change at the Collegiate Level - Todd A. Gilson; Amanda L. Paule-Koba; Emily Ann Heller (University of Kansas Libraries, 2013)
The purpose of this study was to better understand the social-psychological processes and outcomes athletes experience during a head coaching change. The authors conducted semistructured interviews with 47 NCAA Division I athletes, representing 11 different sports at 20 distinct institutions. Following inductive analysis of transcribed interviews, seven higher order themes emerged: emotions, academics, goals, leadership, negative effects, positive effects, and changing culture and structure of the team. According to the perceptions of athletes, results showed that coaches stressed the importance of academics and used goal setting principles with their new team. However, athletes also spoke to deficiencies in leadership and the emotional instability that resulted in a loss of confidence, increased stress, and feeling ignored by the new staff. Thus, open and honest lines of communication need to be formed early with athletes-by multiple athletic personnel-so that individuals have the support system necessary to prevent maladaptive results.